The official National Geographic kids survival guide - Beer, Julie (Children's author) (National Geographic kids., 2026)
"From the experts of exploration--National Geographic--this practical, wide-ranging wilderness survival guide gives kids the know-how to start a fire, build a shelter, escape an avalanche, and so much more!"--